Defining Learning Communities in Undergraduate Medical Education: A National Study. (February 2019) - Shochet, Robert; Fleming, Amy; Wagner, James; Colbert-Getz, Jorie; Bhutiani, Monica; Moynahan, Kevin; Keeley, Meg
Background: Learning communities (LCs) are intentionally designed groups that are actively engaged in learning with and from each other. While gaining prominence in US medical schools, LCs show significant variability in their characteristics across institutions, creating uncertainty about how best to measure their effects. Objective: The aim of this study is to describe the characteristics of medical school LCs by primary purpose, structures, and processes and lay the groundwork for future outcome studies and benchmarking for best practices. Methods: Medical school LC directors from programs affiliated with the Learning Communities Institute (LCI) were sent an online survey of program demographics and activities, and asked to upload a program description or summary of the LC's purpose, goals, and how it functions. Descriptive statistics were computed for survey responses and a qualitative content analysis was performed on program descriptions by 3 authors to identify and categorize emergent themes. Results: Of 28 medical school LCs surveyed, 96% (27) responded, and 25 (89%) provided program descriptions for qualitative content analysis. All programs reported longitudinal relationships between students and faculty. Most frequently cited objectives were advising or mentoring (100%), professional development (96%), courses (96%), social activities (85%), and wellness (82%). Primary purpose themes were supporting students' professional development, fostering a sense of community, and creating a sense of wholeness. Structures included a community framework, subdivisions into smaller units, and governance by faculty and students. Process themes included longitudinal relationships, integrating faculty roles, and connecting students across class years. Conclusions: Medical school LCs represent a collection of high-impact educational practices characterized by community and small-group structures, relational continuity, and collaborative learning as a means to guide and holistically support students in their learning and development as physicians. In describing 27 medical school LCs, this study proposes a unifying framework to facilitate future educational outcomes studies across institutions.